The Influence of Awareness, Knowledge, and Religiosity towards Public Perception of Islamic Banking Usage in Southwestern Afghanistan - Abdullah, Ziarmal; Popal, Ahmad Wali; Tahir, Haris Ahamd (El-Barka, 2024)
High levels of awareness, knowledge, and religiosity are crucial factors in the banking industry, especially for the Sharia-based Islamic banking system. Although Afghanistan is an Islamic country, the participation in Islamic banking (IB) is relatively low, and the factors influencing people's perceptions remain unclear. Therefore, this paper aims to assess the impacts of awareness, knowledge, and religiosity on people's perceptions of using Islamic banking in the southwestern zone of Afghanistan. The study's findings indicate that awareness, knowledge, and religiosity significantly and positively affect people's perceptions in this region. From a policy-making perspective, several measures should be implemented to enhance banking selection criteria, maintain a top position in the market, and compete with conventional banks, which are losing market share due to a lack of awareness. Recommendations include increased investment in marketing and advertising by IB to inform people about their products and services. This approach will significantly contribute to the country's economic growth and the well-being and prosperity of its people.